Uniting in Measures of Common Good: The Construction of Liberal Identities in Central Canada - Poulter, Gillian (Labour / Le Travail, 2010)
The article reviews the book, "Uniting in Measures of Common Good: The Construction of Liberal Identities in Central Canada," by Darren Ferry.
Keywords: 19th century; BOOKS – Reviews; Canada; FERRY; Darren; History; Nonfiction; UNITING in Measures of Common Good: The Construction of Liberal Identities in Central Canada (Book)